Strategi Komunikasi Persuasif Akun Instagram@Diengbersih dalam Meningkatkan Kesadaran Masyarakat Mengenai Kebersihan Lingkungan di Wilayah Dieng - Widiya Arifiyani; Mubarok (INDO PUBLISHING, 2025)
This study aims to identify the persuasive communication strategies used by the Instagram account @diengbersih in raising public awareness regarding environmental cleanliness in the Dieng area. This research applies the S-O-R (Stimulus–Organism–Response) theory as the analytical framework. The study employs a descriptive qualitative method, with data collected through in-depth interviews, direct observation, and content analysis of the @diengbersih Instagram account. The research subjects include community administrators and followers who actively interact with the account.The results indicate that the stimuli delivered through @diengbersih’s Instagram content include documentation of clean-up activities, educational infographics, collaborative campaigns, and calls for participation. The “organism” aspect is reflected in changes in followers’ knowledge, attitudes, and concern toward environmental cleanliness issues. The “response” aspect is shown through active participation in activities, increased positive interactions on social media, and support for cleanliness programs.Based on these findings, it can be concluded that the persuasive communication strategy applied by @diengbersih is relevant and effective in shaping public awareness and encouraging public engagement. The application of the S-O-R theory in this study successfully explains the relationship between the stimuli provided, the audience’s message processing, and the responses generated, making it relevant for understanding the success of social media–based environmental campaigns.